Kajian jenis dan konsentrasi buah terhadap karakteristik fisikokimia dan organoleptik sirup frutty telang - Tri Rahayuningsih; Marina Revitriani; Mujianto mujianto (Agroindustrial Technology, University of Trunojoyo Madura, 2026)
Pure telang syrup has a mild taste and is enhanced with fruit flavours, creating frutty telang syrup. Fruits like pineapple, strawberry, and mango, which grow easily in Indonesia, are used. This study aims to improve the taste of telang syrup by varying fruit types and concentrations. This approach explores the use of locally available fruits as natural flavor enhancers in functional syrup products. The study employed a Randomized Complete Block Design (RCBD) with two factors. The first factor was fruit type (J), consisting of three levels: pineapple, strawberry, and mango. The second factor was fruit concentration (K), with three levels of 30%, 40%, and 50% relative to the solution. Observed parameters included pH, antioxidant activity, viscosity, calories, and sugar content. Organoleptic tests also assessed taste, colour, aroma, and viscosity. Results showed treatment interactions only in viscosity, while other parameters were affected by individual factors. J1K1 achieved the highest taste, colour, and aroma scores, making it the most preferred among panellists. J1K1 (30% pineapple, expectation value 4.87) had pH 6.31, viscosity 6.30 cp, antioxidant activity 42.12%, sugar content 51.08, and 216.63 calories. This study offers recommendations for producing telang syrup with natural fruit flavours and supports the development of functional beverages using locally available ingredients.